Pattern and pathways for mercury lifespan bioaccumulation in Carcinus maenas - Coelho, J. P. (2008)
Carcinus maenas is an important and exploited natural resource in temperate estuaries, being consumed by local populations and also used as fish bait. Through bioaccumulation and bioamplification processes occurring in polluted estuarine ecosystems, this species may directly or indirectly represent a major pathway for Human contamination. No information is available on the overall lifespan bioaccumulation pattern of mercury for this species, which would be an invaluable tool for assessing the risks associated with C. maenas harvest in contaminated areas. Taking that in mind, the main objectives of this work were to clarify the lifespan bioaccumulation pattern of mercury for this species.